DAMPAK SOSIAL MIGRASI TENAGA KERJA KE MALAYSIA - Wini Tamtiari (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1999)
From an economics point of view, the phenomena of migrant workers to Malaysia have more a positive impact than the negative one. Yet, from a different perspective of the social-psychological, there is a main concern of the negative impact suffered particularly by the family of migrant workers in the sending countries. Migrant workers to Malaysia, especially men as head of families, has altered the life patterns of family members left in the sending countries. This turnabout has eventually disturbed a family life which lead to family stress and disruption. The result of the present study carried out at one of the several villages known as a migrant workers pocket in East Lombok show, that the turnabout has influenced a step of divorcement and separation among migrant workers’ families. By and large this occurrence can be recognized from increase divorce rates compared to the prior time of migrant workers mania to Malaysia.